Cerebral Blood Deoxygenation by a Postural Change Detected by Near-Infrared Spectroscopy Has a Close Association with Cerebral Infarction - Irisawa, Hiroshi; Inui, Naoki; Mizushima, Takashi; Watanabe, Hiroshi (Brain sciences, 2022)
Background: The recent introduction of near-infrared spectroscopy has enabled the monitoring of cerebral blood flow in real-time. Previous studies have shown that blood flow velocity is a predictor of cardiovascular disease. We hypothesized that cerebral oxygenation with a change in posture is a predictor for cerebral infarction. We designed a cross-sectional study to investigate the relationship between postural-related changes in cerebral oxygenation and a history of chronic cerebral infarction. Methods: A total of 100 consecutive participants were enrolled in this study. We evaluated changes in cerebral oxygenation with a change in posture from the supine to the upright position in the bilateral forehead. The association between a decline in cerebral oxygenation and chronic cerebral infarction was analyzed with multiple logistic regression adjusted for covariates. Results: Cerebral blood oxygenation increased in 52 participants and decreased in 48 participants with a postural change. The prevalence of decreased cerebral oxygenation was 76.3% in participants with chronic cerebral infarction. Multiple logistic regression analysis showed that a decline in cerebral oxygenation upon a postural change was strongly associated with chronic cerebral infarction (adjusted odds ratio: 3.42, p = 0.025). Conclusions: Cerebral blood oxygenation upon a postural change could be a useful predictor for cerebral infarction.